A new authenticated group key transfer protocol for actual network environment. (4th March 2013) - Wang, Zhiwei
In this paper, we propose a new authenticated group key transfer protocol based on two–layers secret sharing. Our protocol is suitable for the actual network environment, in which there exists a chief server and several sub–servers. The chief server administrates these sub–servers, and each sub–server manages several users. In our protocol, the broadcasted message size is fixed and each group member only needs to compute two small degree interpolating polynomials to recover the group key. Thus, our protocol can be applied for the large size group. Furthermore, we provide authentication for transporting this group key.